Improvement Of Trearment Methods For Hypertrophic Gingivitis In Patients With Epilepsy - Mardonova Dildora Kosimovna (Genius Journals, 2026)
Patients with epilepsy often demonstrate specific oral and periodontal changes associated with antiepileptic drug therapy, particularly gingival hyperthrophy. To evaluate the dental and periodontal status of patients with epilepsy and to substantiate improved approaches to the treatment of hypertrophic gingivitis in this group. Epilepsy and long-term antiepileptic therapy significantly affect periodontal tissues. Improved preventive and therapeutic approaches aimed at early diagnosis and conservative periodontal treatment are required to prevent tooth loss in epileptic patients
Keywords: epilepsy; hypertropic gingivitis; periodontal diseases